Contrasting mycorrhizal functionality in abiotic stress tolerance of woody species - Lauri Laanisto; Nicola Pavanetto; Giacomo Puglielli; Maret Gerz; C. Guillermo Bueno (Scientific Reports)
Abstract Current understanding of how woody plants respond to abiotic stress and how mycorrhizal interactions mitigate this stress is limited, as research has mostly focused on single stress factors. The diverse range of woody plants and mycorrhizal fungi, and the varying intensity and composition of multiple stress factors in different regions worldwide, have made it difficult to study these highly functional symbiotic interactions from a global perspective. Here, we used a top-down approach that involved partitioning known interactions into functional types, and mapping stress tolerances and interactions into overlapping heatmaps. We used a comprehensive dataset of 621 woody species’ tolerance of shade, drought, waterlogging, and cold stress, as well as their mycorrhizal interaction data, to test how stress polytolerance correlates with different functional types of mycorrhiza. We show that single mycorrhizal type associates with shade tolerance, while dual type with cold and waterlogging tolerance. Both arbuscular mycorrhiza and obligate interactions are more abundant in drought stress tolerance conditions, while ectomycorrhiza and facultative interactions are found in more cold and waterlogged stressful conditions. Thus, functionally distinct mycorrhizal interactions form significantly contrasting stress mitigation patterns with woody species, providing insights into both evolutionary and biogeographic patterns related to the development of plant-mycorrhiza interactions.